Laboratory Evaluation and Construction of Fully Recycled Low-Temperature Asphalt for Low-Volume Roads. (25th March 2020) - Raab, Christiane; Partl, Manfred N.
Abstract : Growing economy and increasing pollution evoke the need for more environmentally friendly road construction techniques and the saving of natural resources. In this context, cold recycling plays an important role since, on the one hand, it allows to reduce CO2 emissions drastically and, on the other hand, it offers a variety of opportunities for high percentages of recycling. Inspired by experience in Sweden, the international project "Optimal Recycling of Reclaimed Asphalts for low-traffic Pavement" (ORRAP) for low-volume roads in the Upper Rhine region aims to develop and establish a new strategy for 100% reclaimed asphalt pavement (RAP) at ambient temperature (20°C) without adding virgin bituminous binders or rejuvenators. The still ongoing research project involves laboratory experiments as well as in situ test sections. The link between small-scale laboratory experiments and in situ testing is provided by medium-scale traffic simulation in the laboratory. This paper describes results from medium-scale compaction in the laboratory using different methods as well as traffic simulation with a medium-scale mobile traffic load simulator. The results show that compaction in the laboratory at ambient temperature (20°) is very difficult to achieve. Nevertheless, it was found that compaction at a temperature of 60°C appears possible and provides promising results regarding stability and rutting enabling the in situ construction. The in situ pavement construction at ambient temperature on a low-volume road in Switzerland resulted in a visibly well-compacted and stable base course which was covered by a hot mix asphalt surface course the day after. The test section will be monitored closely over the next 12 months.